A METHODOLOGY FOR DETERMINING AND ANALYZING PERMANENT PROTECTION AREAS OF PROPERTIES DECLARED IN THE RURAL ENVIRONMENTAL REGISTER- CAR - Paula, Danielle Silva de; Ortiz, Jussara de Oliveira; Rosim, Sergio; Namikawa, Laércio Massaru (Boletim de Ciências Geodésicas, 2022)
The Permanent Protection Areas (PPA) are relevant to ensure vegetation around the drainage network. This paper presents an automated methodology for the extraction of drainage from the river and automated generation of PPA, and analysis of environmental adequacy. The methodology is based on geoprocessing and remote sensing techniques applied to RapidEye satellite images. The analyzed area covers a portion of the Paraíba do Sul river basin, located in the city of São José dos Campos (Southern Brazil). Land use and land cover were determined using a digital classifier and estimated within the APP of four rural properties bordering the river. The digital classification of the RapidEye images was evaluated based on the visual interpretation of high spatial resolution airborne orthophotos, as well as through random points that enabled the generation of the Kappa index and global accuracy, showing high agreement. The analysis shows the inadequate land use practice in some properties analyzed, indicating changes in the areas of PPA over the years analyzed. The results of this research show that the proposed methodology can be used for supervision purposes in properties declared in the Rural Environmental Registry (CAR), thus assisting in the decision-making process.